PEMBERDAYAAN PEREMPUAN DIASPORA MELALUI PELATIHAN PODCAST: STUDI KASUS KOMUNITAS “IBU PROFESIONAL REGIONAL ASIA” - Monika Sri Yuliarti (Jurnal Pengabdian Masyarakat Satya Widyakarya, 2025)
This article explores a podcast training initiative as a form of empowerment for diaspora women within the “Ibu Profesional Regional Asia” (IP Asia) community. This community comprises Indonesian women living across various Asian countries, with diverse backgrounds as wives, mothers, and professionals. A situational analysis reveals that diaspora women often face challenges such as social isolation, limited access to non-formal education, and gender stereotypes that hinder their participation in digital technology. In response to these issues, a community engagement program was conducted, offering basic podcast training with a specific focus on the introduction and practical use of Audacity software. The training was held online and attended by active members of IP Asia, particularly from the “Rumah Bermain Public Speaking & Broadcasting”. The results indicate that participants not only acquired fundamental technical skills in podcasting but also experienced increased confidence in self-expression and creative engagement in digital public spaces. This initiative contributed to expanding creative participation opportunities for diaspora women and supported community capacity building through voice-based media. The program highlights the importance of community-based and needs-driven approaches in empowering women in the digital era.